Intravitreal Ranibizumab Alone or in Combination with Calcium Dobesilate for the Treatment of Diabetic Macular Edema in Nonproliferative Diabetic Retinopathy Patients: 12-Month Outcomes of a Retrospective Study - Dongxuan Wang; Hui Wang; Shuang Wu; Xueqiu Yang; Jiansen Xu (International Journal of Clinical Practice)
Objective. This study investigates the efficacy of CaD combined with intravitreal ranibizumab for the treatment of diabetic macular edema (DME) in patients with nonproliferative DR. Methods. This retrospective, observational, case-control study enrolled consecutive patients newly diagnosed with DME. The patients were treated with 3-monthly loading dose injections of intravitreal ranibizumab (IVR) followed by pro re nata injections (3 + PRN), with or without daily oral CaD. The patients were treated and followed up for 12 months. We reviewed their medical records to determine the optical coherence tomography (OCT) findings, number of injections, best-corrected visual acuity (BCVA), and central macular thickness (CMT) at 3, 6, and 12 months after the first injection. Results. We reviewed 102 eyes of 102 patients; 54 patients received IVR combined with oral CaD (IVR + CaD group) and 48 received only IVR (IVR group). In both groups, BCVA was higher, and CMT was lower, at 3, 6, and 12 months after the injection compared to those at the baseline (p<0.05 for all), while there were no significant differences in BCVA improvement or CMT reduction between the two groups (p>0.05). The mean number of IVR injections was significantly lower in the IVR + CaD group than the IVR group (5.4 ± 1.1 vs. 6.7 ± 1.6 injections, p<0.05) during 1 year of treatment. No adverse events were noted in either group. Conclusions. Compared to IVR alone, the addition of oral CaD to IVR in DME patients was safe and effective for improving visual function and restoring the retinal anatomy and was associated with the need for fewer injections.